Mobile hjem - Christensen-Scheel, Boel (Peripeti, 2010)
At the turn of the millennium several contemporary performative practices displayed a specific thematic structure related to the sense of belonging and movement, to the tensions between the local and the global, the social and the material. Two of these practices are here presented as “mobile homes”, and their structure is discussed with help of performance theory, art theory and aesthetic philosophy – concepts such as ‘synaesthetics’, ‘performative paradox’, ‘succession’ and ‘neo-existentialism’ are suggested.